Effects of Acupuncture Combined with Conventional Rehabilitation Training for Patients with Post-Stroke Dysphagia: A Randomized Controlled Trial - Xu F; Zhang Y; Su X; Dai F; Ye Y; Ling M; Hu P; Cheng H (Journal of Multidisciplinary Healthcare, 2025)
Fangyuan Xu,1,* Yiting Zhang,2,* Xingxing Su,2 Fan Dai,1 Yu Ye,3 Meijuan Ling,3 Peijia Hu,4 Hongliang Cheng2 1The First Clinical Medical School, Anhui University of Chinese Medicine, Hefei, 230031, People’s Republic of China; 2Department of Neurology, The Second Affiliated Hospital of Anhui University of Chinese Medicine, Hefei, 230061, People’s Republic of China; 3The Second Clinical Medical School, Anhui University of Chinese Medicine, Hefei, 230031, People’s Republic of China; 4Department of Endocrinology, The Second Affiliated Hospital of Anhui University of Chinese Medicine, Hefei, 230061, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongliang Cheng, Department of Neurology, The Second Affiliated Hospital of Anhui University of Chinese Medicine, No. 300 Shouchun Road, Luyang District, Hefei, Anhui, 230061, People’s Republic of China, Email chl.75811@163.com Peijia Hu, Department of Endocrinology, The Second Affiliated Hospital of Anhui University of Chinese Medicine, No. 300 Shouchun Road, Luyang District, Hefei, Anhui, 230061, People’s Republic of China, Email zjyyhpj@163.comObjective: Stroke is a significant global public health challenge. Evidence suggests that acupuncture contributes to the treatment and rehabilitation of post-stroke dysphagia (PSD), effectively improving swallowing function and enhancing patients’ quality of life. This study aimed to examine the effects of acupuncture combined with conventional rehabilitation training (CRT) on swallowing function, neurotransmitter levels, nutritional status, and swallowing-related quality of life in patients with PSD.Methods: Following screening, 90 patients with PSD were randomly assigned to either the intervention group (receiving acupuncture combined with CRT) or the control group (receiving CRT only). Both groups underwent treatment six times per week for four weeks. Primary outcome measures included the standardized swallowing assessment (SSA), the modified Mann assessment of swallowing ability (MMASA), the water swallowing test (WST), and 5-hydroxytryptamine (5-HT) levels. Secondary outcomes assessed swallowing-related quality of life and nutritional indicators.Results: Compared with baseline data, both groups showed improvements after 2 and 4 weeks of treatment, with reductions in SSA scores and increases in MMASA, hemoglobin (HB), albumin (ALB), serum total protein (STP), swallowing quality of life questionnaire (SWAL-QoL) scores, and WST performance. And the intervention group exhibited significantly greater improvements than the control group at the fourth week. Notably, the 5-HT levels in the intervention group were significantly higher than those in the control group after 4 weeks (362.44± 88.63 vs 310.16± 86.79, P = 0.006).Conclusion: A 4-week course of acupuncture combined with CRT demonstrated significant benefits in enhancing swallowing function, neurotransmitter levels, nutritional status, and quality of life in patients with PSD.Keywords: acupuncture, rehabilitation training, post-stroke dysphagia, clinical trial, swallowing function